Dark Patterns in Web User Interfaces: Toward an Incentive-Based Policy Approach Supplementing Legal Provisions - Torsten J. Gerpott (Wirtschaftsdienst)
Abstract EU and national legislators in the EU continue to generate new regulations, striving to eliminate unfair design patterns in e-commerce, social media and other website user interfaces. This article briefly summarises relevant legal provisions and shows why, despite them, dark design patterns are still frequently found. It concludes that a move beyond a narrow legal dark pattern counter-strategy is required by setting incentives for website providers to implement bright interface design features voluntarily. In Germany, Government support has not been adequate and therefore requires improvement.